Agitated Depression Associated With Flurazepam Discontinuation - Mohamed Salih; Reem Mohamed Osman; Wala Alim; Leena Khalid; Wafa Sosal; Danya Ibrahim; Yassir Mahgoub (Case Reports in Psychiatry)
Agitated depression, also known as melancholia agitata, is a variant of depression characterized by severe symptoms of psychomotor agitation, inner unrest, anxiety, restlessness, prominent vegetative symptoms, and a high risk of suicide. This form of depression is reported to worsen with antidepressants and potentially improve with the use of ECT, lithium, antiepileptics, antipsychotics, and benzodiazepines. We describe a case of a 73-year-old female with a prior history of depression and generalized anxiety disorder who was maintained on flurazepam for 44 years and was admitted for severe depression with psychomotor agitation, prominent vegetative symptoms, thought perseveration, indecisiveness, and psychotic features that emerged following the discontinuation of flurazepam. Symptoms did not resolve with the use of alternative benzodiazepines such as nitrazepam and temazepam and further worsened with the use of several antidepressants. She finally had a complete resolution of these symptoms with a combination of alprazolam, zopiclone, and olanzapine. This case provides insight into this unique variant of depression and the role of GABA agonists in its pathology and management.